Diagnosis of Empathic Abilities of Medical Students - Philipp D. Rasskazov1 , Marina A. Stavruk2 , Lubov A. Kushnyr3 , Anna V. Pichueva3 , Tatiana S. Tsar (Indian Journal of Forensic Medicine & Toxicology, 2020)
The authors of the article focus on empathy as one of the dispositions related to the emotional functioningin the process of communication, which plays an important role in determining success in a profession. Itis believed that people with higher empathy tend to solve professional, personal problems more readily insubject-subject relationships. The technique for diagnosing the empathic abilities of medical students wasbased on a questionnaire developed by V.V. Boyko. Methods of analytical and synthetic study of scientific andmethodological literature, questioning are applied. For empirical data percent distribution and ranking areused. As a result of the study, the following levels of empathic abilities in medical students were evaluated:rational, intuitive, attitudes, penetration, identification. The authors of the article came to the conclusionthat the empathic abilities of medical students are important and influential factors of communication notonly in the doctor-patient model, but also in their interpersonal communication, academic performance ineducational activities.